Early Detection of Bi-ventricular and Atrial Mechanical Dysfunction Using Two-Dimensional Speckle Tracking Echocardiography in Patients with Sarcoidosis - SÜNBÜL, MURAT; TİGEN, MUSTAFA KÜRŞAT (SPRINGER, 2015)
Purpose Sarcoidosis is a systemic inflammatory disease with unknown etiology involving several organs. Myocardial involvement, pericarditis, severe rhythm abnormalities, and heart valve disease due to papillary muscle dysfunction are some of the cardiac manifestations. Conventional echocardiographic methods remain insufficient for the determination of subclinical myocardial dysfunction in patients with sarcoidosis. In our study, we investigated the impact of sarcoidosis on bi-ventricular and atrial functions using two-dimensional (2D) speckle tracking echocardiography (STE). Methods Forty patients with sarcoidosis and 20 age and sex-matched controls were recruited into study. All subjects underwent a transthoracic echocardiography for the evaluation of ventricular and atrial functions with 2D STE. Results Left ventricular (LV) dimensions, LV ejection fraction, and right ventricular (RV) systolic velocity were similar between the two groups. Left atrial (LA) diameter was significantly higher in sarcoidosis patients than controls. Eighteen (45 %) patients in the sarcoidosis group and 1 (5 %) patient in the control group had LV diastolic dysfunction. LV global longitudinal, radial, circumferential strain, twist, untwists, and RV global longitudinal strain values were significantly lower in sarcoidosis patients compared to controls. LA and RA reservoir functions were also significantly lower in sarcoidosis patients than controls. Conclusion Although impaired LV diastolic function was detected using conventional parameters, only novel advanced echocardiographic modalities demonstrated impaired bi-ventricular and atrial mechanical functions in patients with sarcoidosis.
Keywords: Speckle tracking echocardiography; Sarcoidosis; Ventricular function; Atrial function; DIASTOLIC DYSFUNCTION; HEART-FAILURE; VENTRICULAR DYSSYNCHRONY; STRAIN; PULMONARY; DOPPLER